△ A B C is an equilateral triangle with side length s . Point P is in its interior such that P B = 1 3 , P C = 1 4 , P A = 1 5 . If the square of the side length can be expressed as s 2 = a + b c , where a , b , c are positive integers and c is square-free, find a + b + c .
Inspiration: A problem posted by Presh Talwalkar on his channel: Mind Your Decisions
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Similar solution with @Fletcher Mattox 's but easier computation.
Let the centroid of equilateral △ A B C be the origin O ( 0 , 0 ) . Then A ( 0 , 3 s ) , B ( − 2 s , − 2 3 s ) , and C ( 2 s , − 2 3 s ) . Let P ( x , y ) . Then
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ x 2 + ( y − 3 s ) 2 ( x + 2 s ) 2 + ( y + 2 3 s ) 2 ( x − 2 s ) 2 + ( y + 2 3 s ) 2 = 1 5 2 = 1 3 2 = 1 4 2 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
⎩ ⎪ ⎨ ⎪ ⎧ ( 2 ) − ( 3 ) : 2 × ( 1 ) − ( 2 ) − ( 3 ) : − 2 s x = 2 7 − 2 3 s y = 8 5 ⟹ x = − 2 s 2 7 ⟹ y = − 2 3 s 8 5
From ( 1 ) :
4 s 2 2 7 2 + ( − 2 3 s 8 5 − 3 s ) 2 3 s 2 2 3 5 3 − 3 8 5 + 3 s 2 s 2 2 3 5 3 − 5 9 0 + s 2 s 4 − 5 9 0 s 2 + 2 3 5 3 = 2 2 5 = 2 2 5 = 0 = 0
⟹ s 2 = 2 9 5 ± 1 6 8 3 = 2 9 5 + 1 6 8 3 Since 2 9 5 − 1 6 8 3 ≈ 4 . 0 1 5 is too small.
Therefore a + b + c = 2 9 5 + 1 6 8 + 3 = 4 6 6 .
As hinted in the video, rotate the entire diagram 6 0 ° clockwise:
Since ∠ B C P = ∠ A C P ′ , and ∠ A C B = 6 0 ° from equilateral △ A B C , that means ∠ P C P ′ = 6 0 ° . Also, since C P = C P ′ = 1 4 , △ C P P ′ is an isosceles triangle, and since its vertex angle is ∠ P C P ′ = 6 0 ° , it is also an equilateral triangle, which means P P ′ = C P = C P ′ = 1 4 .
Let θ = ∠ A P P ′ . By the law of cosines on △ A P P ′ , cos θ = 2 ⋅ P P ′ ⋅ A P P P ′ 2 + A P 2 − A P ′ 2 = 2 ⋅ 1 4 ⋅ 1 5 1 4 2 + 1 5 2 − 1 3 2 = 5 3 , which means sin θ = 1 − cos 2 θ = 5 4 .
That means cos ∠ A P C = cos ( θ + 6 0 ° ) = cos θ cos 6 0 ° − sin θ sin 6 0 ° = 1 0 1 ( 3 − 4 3 ) .
Finally, by the law of cosines on △ A P C , s 2 = C P 2 + A P 2 − 2 ⋅ C P ⋅ A P ⋅ cos ∠ A P C = 1 4 2 + 1 5 2 − 2 ⋅ 1 4 ⋅ 1 5 ⋅ 1 0 1 ( 3 − 4 3 ) = 2 9 5 + 1 6 8 3 .
Therefore, a = 2 9 5 , b = 1 6 8 , c = 3 , and a + b + c = 4 6 6 .
Use Herons Formula in three of triangle
Problem Loading...
Note Loading...
Set Loading...
I haven't looked at the inspiration video yet, but an obvious (to me) solution is via coordinate geometry.
Let B = ( 0 , 0 ) , C = ( s , 0 ) , A = ( s / 2 , s 3 / 2 )
Then P must lie at the intersection of the circles centered at the vertices:
B: x 2 + y 2 = 1 3 2
C: ( x − s ) 2 + y 2 = 1 4 2
A: ( x − s / 2 ) 2 + ( y − 3 s / 2 ) 2 = 1 5 2
Three equations, three unknowns. solve simultaneously for s :
s = 2 9 5 + 1 6 8 3 , so 2 9 5 + 1 6 8 + 3 = 4 6 6
Now let's see how brutish this solution is compared to the inspiration video ...